Antibacterial Bioactivity of Large Mosquito Fern Azolla filiculoides Lam., 1783 (Pteridophyta: Salviniaceae) Against some Pathogenic Bacteria Isolated from common carp in vitro - Al-Shammari, Nadia A. H.; Abdullah, Jenan N.; Ali, Atheer H.; Al-Janae'e, Ahmed M. S. (Iraqi Journal of Aquaculture, 2023)
Water extract of large mosquito fern Azolla filiculoides used as antibacterial material (as eco-friendly material) against some pathogenic bacteria for common carp Cyprinus carpio. The bacteria represent with Bacillus cereus, Escherichia coli and Staphyllococcus aureus. The results shown that the application of 100% of the stock solution gave better inhibition against the bacteria growth in vitro (25.7, 26.35 and 28.7mm in B. cereus, E. coli and S. aureus, respectively in comparison with other concentrations of water extract of A. filiculoides (25, 50, and 75%). The current encourage results as an inhibition mater against studied bacteria may be applied as alternative eco-friendly material instead of chemical materials to control present and other bacteria pathogenic to fishes.